Evolution of a chronic pain management program in a Northwestern Ontario community: from structural elements to practical application - Hadi Shojaei; Shehnaz Fatima Lakha; Ashley Lyon; Mark Halabecki; Mary Donaghy; Angela Mailis (BMC, 2022)
Abstract Background Chronic pain is a highly prevalent health problem especially in rural regions. There is a dearth of comprehensive pain management programs particularly in rural areas. Aim The objectives of this paper are to describe the evolution of an interprofessional chronic pain team employing a patient-centered model of care with a biopsychosocial approach, and health services metrics. Method This descriptive case study approach includes an overview of the Chronic Pain Management Program (CPMP) services at St. Joseph Care Group in Thunder Bay, NW Ontario; the process involved in the development of an interprofessional chronic pain team employing a patient-centered model of care with a biopsychosocial approach; and metrics of the program's operations. Results Established in 1998, CPMP has evolved to become inter-professional, providing consultations and management, with partial funding by the Ontario Ministry of Health and Long term Care that has allowed expansion of services. The CPMP currently provides three distinct program streams as follows: a) Intensive 6-week, four half-days/week, outpatient program that offers an interdisciplinary team approach in groups and individual format; b) PACE-IT (Pain Assessment Collaborative Education Inter-professional Therapy), 8-week long, half-day/ week, interprofessional treatment program, in person; and c) Individual format for one-on-one services for patients not fitting in either the 6-Week or PACE-IT programs. In addition, Additional services provide virtual consultations and didactic videoteleconference sessions on opioid stewardship and pain management to health providers. Health services outcomes, research, and educational opportunities across the Northwestern Ontario Region, challenges and future needs are discussed. Conclusion The CPMP's model of care can serve as a foundation for expert chronic pain care delivery across rural Canada, and as template for similar institutionally-based and publicly funded pain clinics.